Strategies for Regenerating the Library and Information Profession - Varlejs, Jana (IFLA Publications, 2009)
This volume comprises papers prepared for the 8th World Conference on Continuing Professional Development (Bologna, Italy, 18-20 August 2009). Within the broad theme of creating a positive work environment for a multi-generational workforce in library and information organizations, the conference addresses managing between and across generations, mentoring and coaching, attracting people to the profession and developing a new generation of leaders, re-skilling and transferability of skills, succession planning and passing on knowledge.; Jana Varlejs, Rutgers State University of New Jersey, New Brunswick, USA; Liz Lewis, BBC, London, UK; Graham Walton, Northumbria University, Newcastle upon Tyne, UK.